Pronoun Syllable Elision in Bahasa Indonesia: Case of Casual Speech in Waingapu - Mikaela Indri Malo, Raynesta (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
This paper discusses elision as one of phonological processes in the Indonesian speech, particularly on the use of Bahasa Indonesia in Waingapu, an eastern city in Indonesia. Elision (or deletion) is a term used in phonetics and phonology to refer to the omission of sounds in connected speech, where both consonants and vowels may be affected, and sometimes whole syllables may be elided (Crystal 2008). As in the mostly eastern Indonesia area, in Waingapu, people usually speak at a rapid speed. People tend to simplify words and phrases to ease the pronunciation and meet their needs for easy and fast conversation. This is the main cause of elision to happen. Data is obtained through recordings of daily speeches in various places. This descriptive qualitative study shows syllable elision in almost all pronouns, both as subject and object in a sentence, such as sa from the pronoun saya and ko from the pronoun kau . This elision, combining with other processes, also leads to the creation of new words which function as possessive pronouns as in dia punya becomes de pung and later changed to dem to denote his/her.